Recurrent Mitral Valve Endocarditis Caused by Streptococcus pneumoniae in a Splenectomized Host. (28th December 2013) - Shrestha, Shikha; Chintanaboina, JayaKrishna; Pancholy, Samir
Abstract : A 72-year-old male with a remote history of splenectomy and two previous episodes of pneumococcal endocarditis of mitral valve presented with high-grade fever and confusion for 3 days. Nine months priorly, patient underwent mitral valve repair when he had the first episode of pneumococcal mitral valve endocarditis. He received pneumococcal vaccination two years ago. On examination during this admission, he was found to be febrile (104.3 F) and confused and had a grade 2/6 systolic murmur at the apex without any radiation. Laboratory data was significant for a white blood cell count of 22, 000/mm 3 (normal: 4000–11000/mm 3 ). Blood cultures (4/4 bottles) grew penicillin-sensitive Streptococcus pneumoniae . Transesophageal echocardiogram revealed small vegetation on the posterior mitral leaflet without any evidence of abscess and severe mitral regurgitation. Patient clinically responded to intravenous ceftriaxone. However, due to recurrent pneumococcal mitral valve endocarditis and severe mitral regurgitation, the patient underwent mitral valve replacement. Patient had an uneventful recovery and was discharged home. Pneumococcal endocarditis itself is being uncommon in this current, penicillin, era; our case highlights the recurrent nature of pneumococcal endocarditis in a splenectomized host and the importance of pursuing aggressive treatment options in this clinical scenario.